THE EFFECTIVENESS OF INTEREST-FREE LOAN FINANCING (QARDHUL HASAN) AS THE SOCIAL IMPLEMENTER OF ISLAMIC BANK TO REDUCE POVERTY IN SURAKARTA - Junaidi, Junaidi; Lutfiah, Zeni; Adnan, Moh (Yustisia, 2017)
The function of Islamic banks is not only to eliminate the interest system in its operational system, but also take a role to improve social welfare. Islamic banks have programs that can be used in the context of eradicating poverty, it is interest-free loans (qardhul hasan). Interest-free loan financing (qardhul hasan) is a social loan which is provided free of charge without any charges except returning its capital. This study is intended to examine how the implementation of interest-free loans (qardhul hasan) by Islamic bank and to know the extent of which the financing of interest-free loans (qardhul hasan) can alleviate poverty in the society. This research is none of doctrinal research. The research location is in Islamic bank in Surakarta. The output of this research is publication on national journal.The financing of Al-qardhul hasan itself has not got attention from Islamic bank as the realization of the social function of Islamic banking. Islamic banking products are more oriented to the the programs which contains the value of profit / profit so that interest-free loans (Al-qardhul Hasan) has not taken yet as a role in efforts to alleviate poverty.